A településfejlődés új feltételei - Kőszegfalvi, György (Tér és Társadalom, 1994)
The situation of the settlements, their current history, develópment are defined by objective regularities. At the same time the conscious seftlement development activity, its special means, institutions have a decisive role in influencing the processes of the seftlement development. The processes that took or are taking place after and as a consequence of the systemic change, the new conditions of the socio-economic development play a fundamental impact on the situation of the settlements, the track of their development; a new development behaviour is needed. The past four years are probably inadequate for us to evaluate the favourable or unfavourable processes of the development of settlements in a way that is profound, touches all essential aspects and explores and analyses the correlations. At the same time we cannot deny that some tendencies are shaping. We can recognise – even if not in their entity – some special processes that sign or at least predict the new particular features, the track of the development of the settlements, show the transition of the structure of the system of settlements, transitions of new directions and characteristics. In these processes, besides the transitions deriving from the special self-disciplined development, the new meansand institutional system of the seftlement development has a decisive role. Among these we can consider the formation and function of the seftlement leve] self-governments as the most important factor. We can ask whether the conditions of the seftlement development activities done by the local self-governments were fully created and provided during the past few years. We can hardly say ’yes’ to the above question. It is well known that the access to the financial means necessary for the maintenance of the operation of the settlements and their development have always been very limited. In a significant number of settlements only the most essential financial means of the operation could be gathered, provided. It was not only the limited scales of the financial means, the inadequacy of the resources that held back the formation, effectiveness of (more) complete settlement development activities of the local self-governments, other conditions were also either missing or not provided in a satisfactory amount. No law on regional and settlement development was passed. It is very disappointing that the malter of settlement development is not dealt with in accordance with its importance, weight. An unfavourable factor affecting the operation and development of the settlements is the uncertainty, or we can say, the lack of the medium levei in the system of control of the public administration. The role of the settlements is decisive in the building of any model of public administration, whether it is about the restructuring, modernisation of the county system or the formation of a new system of control built on regions. A fundamental criterion in the case of either solution is the bottom-up building, the basis of which is the settlements. The means and institutions of legal control have a stressed importance. For the comprehensive management, control of the complex settlement development activity a settlement development act is/should be necessary. The Local Government Act should be amended, developed further. The role, contribution, division of labour of the branches in settlement development should have legal regulation. The necessary harmony of the certain acts in issues concerning settlement development should be created. The economic matters of the settlement development activities done by the local self-governments need a new regulation, too; this regards the issues concerning the utilisation of the property of the self-government, the faster and more concerted development of the local infrastructure, the co-operation between settlements. There is a case for the approach, management of the technical tasks of the settlement development on new grounds. A newtype settlement planning and up-to-date construction regulations are needed.